Tarekat: sejarah dan perkembangannya di indonesia - husada, moch nazar aditia (Maliki Interdisciplinary Journal, 2025)
The tarekat (Sufi orders) represent a significant aspect of Islamic tradition, originating from the development of Sufism since the early Hijri era. This study aims to explain the origins of tarekat, explore the relationship between tarekat and theosophy, and map the growth of major tarekat in Indonesia, particularly Qadariyah, Naqsyabandiyah, and Syadziliyyah. The research employs a qualitative method with a historical approach, through literature review and archival documentation. The findings show that tarekat function not only as a spiritual path but also as a social institution shaping the religious identity and culture of Muslim communities in Indonesia. The relationship between tarekat and theosophy adds philosophical and spiritual dimensions, making tarekat a means of mystical knowledge integrated with religious and social practices. This comprehensive approach fills gaps in previous research and highlights how tarekat adapt to challenges in the modern era. The study recommends further field research to deepen understanding of the role of tarekat in contemporary society.